Use of digital media and its impact on generation Y & Z - Ordoñez Guartazaca, Marjorie (Revista Universidad de Guayaquil, 2019)
The present research raises what is the behavior of certain Y & Z generations in the use ofdigital media, and how this influences the new generations through close interaction with thestudents of the University of Guayaquil of the Faculty of Administrative Sciences, in order toanalyze their behavior when using digital media. The quantitative methodology was used togather information through the surveys. The main results show the incidence of the use ofdigital media in both generations and its importance in the development of the interconnecteddigital society.
Keywords: Generation Y; Generation Z; Digital Media